2004
DOI: 10.5194/angeo-22-3021-2004
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of wave mode identification techniques

Abstract: Abstract. The four point measurements available from the Cluster mission enable spatiotemporal effects in data sets to be resolved. One application of these multipoint measurements is the determination of the wave vectors and hence the identification of wave modes that exist within the plasma. Prior to multi-satellite missions, wave identification techniques were based upon the interpretation of observational data using theoretically defined relations. However, such techniques are limited by the quality of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 21 publications
4
53
0
Order By: Relevance
“…Our time interval is shorter and is free of such reversals, which yields a more accurate estimation of the average flow speed. Second, there are intrinsic differences between the two methods (the k-filtering and the phase difference) used to estimate the characteristic of the waves [Walker et al, 2004]. For instance, Chaston et al [2005] claim to resolve scales smaller than the spacecraft separations and also analyzed frequencies up to 10 Hz in the spacecraft frame (these limits were not discussed by Chaston et al [2009]), which most likely involve spatial aliases as shown by Sahraoui et al [2010].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our time interval is shorter and is free of such reversals, which yields a more accurate estimation of the average flow speed. Second, there are intrinsic differences between the two methods (the k-filtering and the phase difference) used to estimate the characteristic of the waves [Walker et al, 2004]. For instance, Chaston et al [2005] claim to resolve scales smaller than the spacecraft separations and also analyzed frequencies up to 10 Hz in the spacecraft frame (these limits were not discussed by Chaston et al [2009]), which most likely involve spatial aliases as shown by Sahraoui et al [2010].…”
Section: Discussionmentioning
confidence: 99%
“…Borg et al [2005] and Chaston et al [2009] have studied this event and confirmed that the Cluster spacecraft encountered a diffusion region around 2330 UT. Chaston et al [2009] have, furthermore, estimated the wave vectors of the fluctuations using an interferometry method that makes use of measured phase differences between the satellites [Walker et al, 2004]. They showed that waves observed in the diffusion region were consistent with KAWs.…”
Section: Introductionmentioning
confidence: 99%
“…The highly changeable nature of the waves for this particular interval was already noticed by Walker et al (2004). The nature of the waves differs from interval to interval and from frequency to frequency for a given interval.…”
Section: Statistical Studymentioning
confidence: 87%
“…Tjulin et al (2005) confirm the presence of mirror modes for the same interval by analyzing the electric field fluctuations after using both magnetic and electric field as input for the k-filtering. Walker et al (2004) compare the results obtained via k-filtering with those obtained via phase differencing method (Balikhin et al, 1997) applied to the same 164 s data interval. They find a mixture of slow, Alfvén and mirror waves with their wave vectors close to the orthogonal direction to the average magnetic field.…”
Section: Magnetosheath Crossingmentioning
confidence: 99%
“…Matsui et al (2007) applied a phase differencing technique to Cluster observations to study broadband ULF waves near the dayside polar cap boundary. For a detailed comparison of the phase differencing approach with the k-filtering technique using Cluster STAFF and EFW measurements, the reader is referred to Walker et al (2004). For a review of the wave distribution determination problem, see Storey (1999).…”
Section: Introductionmentioning
confidence: 99%